The Export-Led Growth: A Case Study of Costa Rica - Gokmenoglu, Korhan K.; Sehnaz, Zehra; Taspinar, Nigar (Elsevier Science Bv, 2015)
This paper empirically investigates the export-led growth hypothesis for Costa Rica. Johansen co-integration and Granger Causality tests are employed to investigate the long-run relationship and causality between exports and economic growth respectively. The results of Johansen co-integration indicate a long-run equilibrium relationship between exports and economic growth. Granger causality test results show an unidirectional causality from economic growth to export growth of Costa Rica. (C) 2015 The Authors. Published by Elsevier B.V.
16th Annual Conference on Finance and Accounting (ACFA) -- MAY 29, 2015 -- Prague, CZECH REPUBLIC
Keywords: Export-led Growth; Granger causality; Johansen co-integration; Costa Rica